Effects of Housing Locations on Feather Damages of Laying Hens in a Free-Range Housing System - PETEK, METIN (Journal of the Hellenic Veterinary Medical Society, 2021)
This study was made to evaluate the effects of different locations of a free range housing system on feather damages of laying hens. The experimental house consisted of three different locations as closed indoor plastic slats, closed indoor litter and outdoor range area. The birds were able to move freely between the locations of the experimental house and they had continuous access to outdoor range during the day. The feather damages of the birds was evaluated with a distance scoring system at 64 weeks of age. Five area in each location of the experimental house were determined at first and then feather damages of five body parts of ten birds in each location were scored to measure plumage quality. Total feather score was defined as the sum of the scores of five body parts of the birds. Best plumage quality was measured in neck in all housing locations (P<0.01, P<0.05 and P<0.01) and total feather score of the birds was significantly greatest (worst) in slats (P<0.05).